Assessment of Plaque pH after Oral Rinsing with Four Customary Used Types of Complementary Infant Formula - Ali Nozari; faezeh ghaderi; Elmira Niaz; Zhale Salehipour (Mashhad University of Medical Sciences, 2018)
Background: Complementary infant formulas are the second most important sources of nutrition for neonates after breast milk. Considering the cariogenic potential of infant formulas, selection of these nutritive sources should be safe to reduce the risk of baby bottle syndrome in newborns. The present study aimed to estimate the plaque pH changes after rinsing with four customary used types of complementary infant formula. Methods: An in-vivo, in-vitro study was conducted on five healthy neonates aged 12-18 months to assess the plaque pH changes caused by rinsing with four different types of complementary infant formula, including Rice and Milk Cerelac, Wheat and Milk Cerelac, Banana and Milk Humana, and Peach and Milk Humana. Data analysis was performed in SPSS version 17 using paired t-test to compare the pH changes associated with each formula. In all the statistical analyses, P-value of less than 0.01 was considered significant. Results: All the formulas significantly reduced the plaque pH to less than the pre-rinse pH. However, the plaque pH decreased to less than the critical pH level (